Correlative light microscopy for high-content screening - Flottmann, Benjamin; Gunkel, Manuel; Lisauskas, Tautvydas; Heilemann, Mike; Starkuviene-Erfle, Vytaute; Reymann, Jürgen; Erfle, Holger (BioTechniques, 2013)
High-throughput microscopy is an effective tool for rapidly collecting data on a large scale. However, high throughput comes at the cost of low spatial resolution. Here we introduce correlative light microscopy by combining fast automated widefield imaging, confocal microscopy and super-resolution microscopy. We demonstrate the potential of this approach for scalable experiments. The workflow consists of a robust approach for selecting cells of interest on a wide-field screening microscope at low resolution and subsequently re-localizing those cells with micrometer precision for confocal and super-resolution imaging. As a case study, we visualized and quantified cis- and trans-Golgi markers at increasing resolution.